2020
DOI: 10.3389/fchem.2020.00051
|View full text |Cite
|
Sign up to set email alerts
|

Pristine and Hydroxylated Fullerenes Prevent the Aggregation of Human Islet Amyloid Polypeptide and Display Different Inhibitory Mechanisms

Abstract: Protein aggregation, involving the formation of dimers, oligomers, and fibrils, is associated with many human diseases. Type 2 diabetes is one of the common amyloidosis and linked with the aggregation of human islet amyloid polypeptide (hIAPP). A series of nanoparticles are reported to be able to interact with proteins and enhance/inhibit protein aggregation. However, the effects of C 60 (a model system of hydrophobic nanoparticle) and C 60 (OH) 8 (a hydroxylated fullerene) on hIAPP aggregation remain unknown.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 69 publications
1
22
0
Order By: Relevance
“…If we consider the extended π-system of the fullerene, it is not surprising that aromatic amino acids such as tryptophan, tyrosine, phenylalanine, and histidine interacted the most with it ( Figure 3 ) [ 20 , 24 , 33 , 34 , 35 , 39 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 ]. In particular, Trp exhibited the largest value of binding energy among the twenty proteinogenic amino acids.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…If we consider the extended π-system of the fullerene, it is not surprising that aromatic amino acids such as tryptophan, tyrosine, phenylalanine, and histidine interacted the most with it ( Figure 3 ) [ 20 , 24 , 33 , 34 , 35 , 39 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 ]. In particular, Trp exhibited the largest value of binding energy among the twenty proteinogenic amino acids.…”
Section: Resultsmentioning
confidence: 99%
“…In protein/peptide-fullerene complexes, several aliphatic residues are usually part of the C 60 binding pocket and contribute to binding [ 33 , 35 , 49 ]. Hydrophobic interactions can be established with methionine, valine, isoleucine, leucine, proline, alanine, and glycine ( Figure 6 ).…”
Section: Resultsmentioning
confidence: 99%
“…GQDs for in vivo mitigation of T2D amyloidosis.By combining all-atom REMD and MD simulations, AFM and TEM images, ThT and cell toxicity assays, Mo et al[957][958][959] examined the influences of hydroxylated carbon nanotubes and fullerenes on the fibrillization of hIAPP. REMD and MD simulations demonstrated that both CNT-OHs and C60OHs not only suppress the formation of β-sheet and β-hairpin-containing amyloidogenic precursor of hIAPP, but also remodel or disassemble preformed hIAPP protofibrils/fibrils.…”
mentioning
confidence: 99%
“…Our analysis shows that the average CSA values are 489.48 Å 2 in the S_RBD in the presence of Cefuroxime system, 617.884 Å 2 in the S_RBD in the presence of Erythromycin system, 560.749 Å 2 in the S_RBD in the presence of Lincomycin system, and 546.891 Å 2 in the S_RBD with Ofloxacin system, respectively, as described in Figure 4C. These demonstrate a comparatively stronger binding affinity between S_RBD and Erythromycin/Lincomycin than the other systems [53]. The CSA value of Erythromycin and S_RBD is even larger, because the molecular weight and the surface of Erythromycin is larger than other molecules.…”
Section: The Conformational Difference Of S_rbd In Different Research Systemsmentioning
confidence: 70%